Difference In Blood Pressure and After Slow Deep Breathing Therapy In Hypertensive Patient At The Elderly Integrated Health Post - Fitriyah, Fitriyah; Kustin, Kustin; Nafista, Ulfia Fitriani (Journal of Nursing Periodic, 2025)
Introduction:According to WHO data, the prevalence of hypertension in the elderly is 29%, with Indonesia ranging from 26% to 31%. In East Java, the prevalence is 26.2%, while Jember Regency has 198,562 residents in the Sukowono area, ranking second in hypertension cases. Data from the elderly posyandu in Sumber Wringin Village shows that 10.3% of elderly individuals suffer from hypertension. Managing hypertension in the elderly requires treatment options that minimize side effects while preventing morbidity, mortality, and maintaining normal blood pressure. One effective technique is slow deep breathing therapy. This study aimed to examine the difference in blood pressure before and after administering slow deep breathing therapy to hypertensive patients at the elderly posyandu. Methods: This research employed a pre-experimental design with a one-group pretest-posttest approach. The study population consisted of 40 hypertensive patients at the elderly posyandu, with a sample size of 36 individuals selected through simple random sampling. Results: Data collection involved observation sheets and blood pressure measurements. The data were analyzed using the Wilcoxon signed-rank test. Before the intervention, the majority of respondents (58.3%) were categorized as having severe hypertension. After the intervention, 55.6% of respondents experienced moderate hypertension. Statistical analysis showed a significant difference in blood pressure before and after slow deep breathing therapy, with a p-value of 0.000 (<0.05). Conclusion: Slow deep breathing therapy effectively reduces blood pressure in hypertensive elderly patients at the posyandu. It is recommended for hypertension management, with a duration of 10–15 minutes per session, performed twice daily in the morning and evening, to promote sustained blood pressure improvements.